Analisis Sensitivitas Permodelan GR4J Terhadap Pengalihragaman Data Hujan Menjadi Debit Pada DAS Indragiri (Studi Kasus AWLR Lubuk Ambacang) - Fauzi Febriansyah; Manyuk Fauzi; Imam Suprayogi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The aim of study research is to analyze performance of GR4J (Ge'nie Rurala`4parame`tres Journalier) on Indragiri’s Basin. GR4J is one of conceptual model for rainfall-runoff prediction. The method of study research are running using default value and variation of length data for calibration and verification. There are 9 scheme in variation of length data. Input data for this model are daily data of rainfall at the Tanjung Pati station and Sijunjung Station, daily data of evaptranspiration potential which is the result of Cropwat program with input climatology data at Sentajo Station and daily data of discharge observation at Lubuk Ambacang Station for test modeling result. The result show that GR4J performance is better than GR3J performance with X1= 1185,20 mm, X2 = -1,0 mm, X3 = 217,11 mm, and X4 = 1,1 day. Such thing reviewed by assessing the Nash-sutcliffe (R2) and Coefficients Correlation(R) that have better performance. R2 and R parameters in GR4J are 63,44% and 0,61.Keywords:GR4J,calibration, verification, GR3J